The Effect of L-Carnitine and Coenzyme Q10 on the Sperm Motility, DNA Fragmentation, Chromatin Structure and Oxygen Free Radicals During, before and after Freezing in Oligospermia Men - Chavoshi Nezhad, Negin; Vahabzadeh, Zakaria; Allahveisie, Azra; Rahmani, Khaled; Raoofi, Amir; Rezaie, Mohammad Jafar; Rezaei , Masoumeh; Partovyan, Maria (Urology Journal, 2021)
Purpose: The aim of the present study is to assess the effect of L-carnitine and Coenzyme Q10 (CoQ10) on human sperm motility, DNA fragmentation, chromatin structure, and reactive oxygen species (ROS) during, before and after freezing in oligospermia men. Materials and Methods: Semen was collected from 30 oligospermic men, who referred to infertility clinic of Beasat Hospital in Sanandaj, Iran. The samples of each individual were divided into 8 equal parts: 1. control group before freezing; 2. incubated with L-carnitine; 3. incubated with coenzyme Q10; 4. incubated with the combination of L-carnitine + CoQ10; 5. control freezing group; 6. the experimental freezing group with L-carnitine; 7. the experimental freezing group with coenzyme Q10 and 8. the experimental freezing with the combination of L-c + CoQ10. Sperm motility was assessed by WET MOUNT method. DNA fragmentation was evaluated by SCD (Sperm Chromatin Desperation), ROS, was evaluated by quantitative fluorescence reaction, and chromatin deficiency was determined by chromatin staining (CMA3). Results: Antioxidant treatments, significantly reduced the number of ROS + in the pre and post freezing groups. Significant improvement was seen in the sperm motility of class B in the pre freezing groups with L-carnitine. Antioxidants also reduced the percentage of DNA fragmentation and protamine deficiency in pre-and post-freezing. Conclusion: Addition of Coq10 and L-carnitine to human sperm medium significantly reduced the number of ROS. This reduction in ROS reduced sperm damage during cryopreservation.